Realizing superior cycling stability of Ni-Rich layered cathode by combination of grain boundary engineering and surface coating. (August 2019) - Cheng, Xiaopeng; Zheng, Jianming; Lu, Junxia; Li, Yonghe; Yan, Pengfei; Zhang, Yuefei
Abstract: Ni-rich layered lithium transition metal oxides are promising cathode materials for the next generation high energy density lithium ion batteries. However, high Ni content leads to severe side reactions at cathode/electrolyte interface, coupled with mechanical disintegration significantly degrading the electrochemical performance and safety. Surface coating and grain boundary (GB) engineering can respectively protect surface layer and suppress cracking issue, but direct comparisons of the individual effect of the two methods at different cycling conditions has not been fully explored. Moreover, the two methods have never been coupled together previously, let alone their coupling effect. Herein, we take LiNi0·8 Mn0·1 Co0·1 O2 as a model material and utilize atomic layer deposition coating and annealing protocol to demonstrate the individual and coupling effects of surface coating and GB engineering on cycling stability. GB engineering is found to be more effective than surface coating in enhancing cycling stability due to suppressed intergranular cracks. Promisingly, coupling GB engineering and surface coating, we can achieve superior cycle stability even upon high voltage cycling (91% retention after 200 cycles at 2.7–4.7 V), which demonstrates the importance to simultaneously alleviate surface degradation and bulk disintegration in design of advanced cathode materials. Graphical abstract: The individual effect of surface coating and GB engineering as well as their coupling enhancement on cycling stability are investigated by using the LiNi0·8 Mn0·1 Co0·1 O2 as a model cathode. We find that suppressing crack is more crucial for achieving superior cycling stability. The combination of surface coating and GB engineering enables a much improved capacity retention at high voltage cycling. By utilizing advanced characterization tools, the structure-property relationship is revealed.Image 1 Highlights: Compared the individual effect of surface coating and GB engineering in stabilizing layered cathode. GB engineering improves the capacity retention of NMC811 from 52% to 74% in a full cell test at 2.7–4.4 V after 500 cycles. Realized 91% capacity retention at 2.7–4.7 V after 200 cycles by coupling surface coating and GB engineering.